Support for regulatory and voluntary approaches to wildfire adaptation among unincorporated wildland-urban interface communities. (February 2020) - Edgeley, Catrin M.; Paveglio, Travis B.; Williams, Daniel R.
Highlights: We conducted focus groups in two wildland-urban interface communities. Discussions focused on support for regulatory and voluntary wildfire risk reduction. Low support for regulation stems from unique factors in each community. Absence of collective action led to support for larger-scale approaches. Education may not alleviate community opposition to wildfire regulation. Abstract: Regulation of building standards and residential development practices in the wildland-urban interface (WUI) is increasingly advocated as a possible avenue for wildfire risk reduction. However, many documented instances of successful wildfire adaptation occur in incorporated communities with local governments or formalized structures for channeling such efforts. Less research has explored whether regulatory approaches might be a viable option for adaptation in unincorporated communities without local governments, particularly from the perspective of community members and local professionals. The research presented here attempts to understand strategies, programs or incentives that local residents think would best advance fire adaptation in their communities given local social context, with a focus on both regulatory and voluntary approaches. Data presented come from focus groups of residents and professionals in Story, Wyoming, and Timber Lakes, Utah. Participants in both communities displayed low support for regulatory approaches due to distrust in local, state, or federal governments, preferring instead to conduct wildfire risk reduction activities on a voluntary basis. Each population was willing to consider regulatory approaches only if associated standards or policies were specifically tailored to their community, channeled through a trusted organizing body and organized by community leaders. Residents were interested in regulatory efforts that allowed community members the opportunity to act at the local level, govern efforts themselves, and produce tangible benefits for their community. We discuss implications for identifying appropriate voluntary and regulatory wildfire risk reduction approaches in unincorporated or rural communities and provide suggestions for encouraging collective action in similar local contexts.